Cyanide-bridged FeIII-CuII complexes: Jahn-Teller isomerism and its influence on the magnetic properties - Atanasov, Mihail; Comba, Peter; Helmle, Stefan (Inorganic chemistry, 2012)
We report here the synthesis and characterization of four dinuclear cyanide-bridged FeIII-CuII complexes, based on a tetra- or a pentadentate bispidine ligand (L1 or L2, respectively; bispidines are 3,7-diazabiyclo[3.3.1]nonane derivatives) coordinated to the CuII center, and a tridentate bipyridineamide (bpca) coordinated to the low-spin FeIII site, with cyanide groups completing the two coordination spheres, one of them bridging between the two metal ions. The four structurally characterized complexes [{Fe(bpca)(CN)3}{Cu(L1·H2O)}]BF4, [{Fe(bpca)(CN)3}{Cu(L2)}][Fe(bpca)(CN)3]·5H2O, [{Fe(bpca)(CN)3}{Cu(L2·MeOH)}]PF6·MeOH·H2O, and [{Fe(bpca)(CN)3}{Cu(L2)}]PF6·2H2O belong to different structural isomers. The most important differences are structurally and electronically enforced (direction of the pseudo-Jahn-Teller mode) strong or weak interactions of the copper(II) center with the cyanide bridge. The related strength of the magnetic coupling of the two centers is analyzed with a combination of experimental magnetic, electron paramagnetic resonance (EPR), electronic spectroscopic data together with a ligand-field theory- and density functional theory (DFT)-based analysis.